LIPOSOMAL MEDIATED ANTIGEN DELIVERY: ISOLATION AND CHARACTERIZATION (International Journal of Food and Nutritional Sciences, 2022)
Objective: The present study was aimed on developing and characterizing Liposomal Delivery System loaded with antigen; filaria parasite extracted protein for better sustain release antigen profile. Methods: Liposomes were prepared by Reverse Phase Evaporation (REV) method (Szoka and Papahadjopolus; 1978) with slight modification using molar ratio of Soya PC:PE:Cholesterol in different molar concentration.Results: In the present study the storage stability of the vesicles was determined by measuring the vesicle size, residual antigen content and antigen integrity before and after 30 Days at 4±1ºC and 25±1ºC. In Soya PC:PE:CH liposomes only a slight increase in size on storage at 25±1ºC and insignificant change in size on storage at temperature 4±1ºC occur, indicate that Soya PC:PE:CH liposome are more stable than conventional Soya PC:CH liposomes. Percent of residual antigen remain in liposomes by assuming the initial content to be 100%, in Soya PC:PE:CH liposomes only 14-15% antigen was lost at temperature 25±1ºC and 5-6% antigen was lost on storage at 4±1ºC. Antigen integrity was evaluated by performing the SDS -PAGE of the liposome formulations. (Optimized CL3 formulation stored at 4±1ºC) after 30 Days. Antigens were found to be intact in the formulation stored at 4±1ºC after 30 days. There was no effect of storage on structural integrity of the antigen (fig; 9.5B and fig; 9.5C).